(untitled) (World of finance, 2021)
Introduction. Such criminogenic phenomena as shadowing and monopolization of the economy, legalization (laundering) of criminally obtained property are intensifying today in Ukraine. Recent changes in legislation and prospects for reforming fiscal and law enforcement institutions require a permanent study of the state of prevention, detection and investigation of financial crimes in the fiscal sphere. In this context, an important task is to create a single institution with appropriate functions, rights and powers. The purpose of the article is to identify real and possible risks for the formation of effective optimal directions for ensuring the economic security of Ukraine based on the analysis of the peculiarities of the processes of prevention, detection, termination, investigation and detection of financial crimes in the fiscal sphere. Methods. A number of general and special research methods were used in the study of the prevention, detection and investigation of financial crimes in the fiscal sphere, in particular: analysis, synthesis, induction, deduction, abstract-logical method and generalization method. Results. The necessity of creating a single institution for the prevention, detection and investigation of financial crimes, including in the fiscal sphere, is substantiated. Based on government statistics, the eight most popular tax avoidance schemes in Ukraine have been identified, leading to total budget losses. The structure of predicate crimes in court convictions in recent years is analyzed, and the main types of predicate crimes in the fiscal sphere are outlined. It is proved that in Ukrainian practice the number of criminal proceedings for tax evasion, brought to sentencing and prosecution decreases sharply, which indicates: the actual impunity for committing crimes in the fiscal sphere; inaction or excess of authority, improper investigation by the persons investigating these crimes, the presence of a corruption component in the pre-trial investigation; incompetence of investigators (detectives) investigating crimes in the fiscal sphere, as well as insufficient level of knowledge in the fiscal sphere of prosecutors as procedural managers. This made it possible to argue the feasibility of creating an economic security bureau. Based on the analysis of the dispositions of the articles of the Special Part of the Criminal Code of Ukraine, twelve articles have been identified that should be classified as tax crimes. Perspectives. Further research should focus on finding the best approach to addressing the issue of financial crime in the fiscal sphere, as well as to ensure the appropriate level of economic security in Ukraine.